Implant Surface Modifications: A Review - Hemlata Garg; Gaurav Bedi; Arvind Garg (Journal of Clinical and Diagnostic Research, 2012)
The aim of the present review was to elaborate on the surface modifications of biomaterials which are used in implant dentistry. The ongoing studies on the clinical and laboratory phases and on the biomaterial sciences have largely aimed at invoking a stronger bone response and an earlier and longer functional loading. Surgical grafting procedures to improve the bone bed are used to create an ideal environment for the implant functioning. The implant selection which is based on the available bone, is also an important determiner of the long term clinical success. The interfacial zone between the implant and the bone is composed of a relatively thin layer (<100um) which consists of heterogenous metallic oxide, proteins and connective tissue. The integrity of the implant – tissue interface is dependent on the material and on mechanical, chemical, surface, biological and local environmental factors, all of which change as a function of time in vivo. Because a stable interface must be developed before the loading, it is desirable that the tissue apposition may be accelerated to the implant surface. The material developments that have been implemented in the clinical practice include the use of surface roughened implants and bioactive ceramic coatings. Osseointegration occurs around the screw threaded implants through the tissue ongrowth or through a direct apposition between the tissue and the implant surface. The alternative methods of the implant-tissue attachments, based on the tissue ingrowth into roughened or three dimensional surface layers, yield a higher bone metal shear strength and decreased implant loosening. A positive effect of various surface modifications which are illustrated in this review, has been observed and suggested by many groups.